Two-Stage Separator Level Coupling Control Based on ASFW-DDPG Algorithm - Xiaoyong He; Han Pang; Boying Liu; Yuqing Chen (IEEE Access)
The significant fluctuations in the liquid level of the two-stage tandem separators on FPSOs result in low oil and gas separation efficiency. To address this issue, an improved adaptive smoothing factor weight deep deterministic policy gradient (ASFW-DDPG) control algorithm is proposed to mitigate the separator liquid level fluctuations. The adaptive smoothing factor weight function and the reward function are meticulously designed to improve convergence speed and stability. A two-stage tandem separator liquid level control network, based on the ASFW-DDPG online control algorithm, is developed. Simulation experiments with the ASFW-DDPG algorithm are carried out using monitoring data from the separators on FPSOs. These simulations demonstrate that the learning efficiency of the ASFW-DDPG algorithm is 200% higher than that of the traditional DDPG algorithm. The primary and secondary separator liquid levels stabilize at the set values within 2.4 seconds and 1.8 seconds, while the PID and traditional DDPG algorithms exhibit slight fluctuations in liquid level. The results suggest that the ASFW-DDPG algorithm exhibits superior convergence speed and stability.